2023
DOI: 10.1038/s41392-023-01431-6
|View full text |Cite
|
Sign up to set email alerts
|

CNTNAP2 intracellular domain (CICD) generated by γ-secretase cleavage improves autism-related behaviors

Jing Zhang,
Fang Cai,
Renbin Lu
et al.

Abstract: As the most prevalent neurodevelopmental disorders in children, autism spectrum disorders (ASD) are characterized by deficits in language development, social interaction, and repetitive behaviors or inflexible interests. Contactin associated protein like 2 (CNTNAP2), encoding a single transmembrane protein (CNTNAP2) with 1331 amino acid residues, is a widely validated ASD-susceptible gene. Cntnap2-deficient mice also show core autism-relevant behaviors, including the social deficits and repetitive behavior. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Our teams and others also reported impaired hypothalamic regulation in Magel2 KO mice with abnormal oxytocin (OT) maturation (10,14,18,19), and disrupted development and function of pro-opiomelanocortin (POMC) neurons (19,20). Necdin KO mice display variable lethality after birth (21,22) due to respiratory distress (23), growth retardation, motor deficit in infancy (24), sensory deficits (25), high scraping, cognitive alterations (22) and alterations of social and circadian behaviors (26,27). At the neuroanatomical level, Necdin KO mice display a reduction in the number of OT and gonadotropin-releasing hormone (GnRH)-producing neurons, alterations in perinatal serotonergic metabolism and development (22,28), and alterations in clock gene expression (26).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our teams and others also reported impaired hypothalamic regulation in Magel2 KO mice with abnormal oxytocin (OT) maturation (10,14,18,19), and disrupted development and function of pro-opiomelanocortin (POMC) neurons (19,20). Necdin KO mice display variable lethality after birth (21,22) due to respiratory distress (23), growth retardation, motor deficit in infancy (24), sensory deficits (25), high scraping, cognitive alterations (22) and alterations of social and circadian behaviors (26,27). At the neuroanatomical level, Necdin KO mice display a reduction in the number of OT and gonadotropin-releasing hormone (GnRH)-producing neurons, alterations in perinatal serotonergic metabolism and development (22,28), and alterations in clock gene expression (26).…”
Section: Introductionmentioning
confidence: 75%
“…Behavioural changes are present throughout the patient's life. Anxiety, interactions with novel objects or social interactions are altered in Necdin (27) and Magel2 KO mice (14,17), with a variability in the severity of the phenotype, partly due to the environmental context. Madin KO mice showed a preference for the novel object versus a familiar one and for a congener mouse versus an empty cage.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that CICD enters the nucleus and functions as a transcription factor to improve autism-related behaviors. 31 Therefore, disruptions in the α-cleavage of CNTNAP2, such as by pathogenic mutations shown in Fig. 4, may affect the downstream CNTNAP2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…30 Recently, we found that CNTNAP2 is cleaved by presenilins-dependent γ-secretase to produce the CNTNAP2 intracellular domain (CICD), and expression of the CICD improves autism-like behaviors. 31 Our current study reveals that in addition to its γ-secretase cleavage, CNTNAP2 undergoes complex proteolytic processing by furin and a disintegrin and metalloproteinase (ADAM)10/17-dependent α-secretase. The main α-cleavage product C79 by ADAM10 is required for the subsequent γ-secretase cleavage to generate the CICD.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation